Correlation between small earthquakes and CO2 anomalies in spring waters: a statistical experiment on the probability of seismic occurrence - Fidani, C.; Gherardi, F.; Facca, G.; Pierotti, L. (Frontiers in Earth Science, 2023)
We correlated carbon dioxide (𝐶𝑂 2 ) time series detected at the Gallicano site in Tuscany, Italy, with low-magnitude earthquakes occurred in the surrounding area between 2017 and 2021. The 𝐶𝑂 2 irregular component distribution was analyzed by a Pearson type VII fit, and its cumulate probability by the Gauss's hypergeometric function, to statistically evidence anomalous fluctuations. We calculated the Matthews correlation between gas concentrations and low-magnitude earthquakes by defining a binary occurrence of 𝐶𝑂 2 anomalies and seismic events. A positive correlation was highlighted by a time lag between the digital series, which resulted in 𝐶𝑂 2 anomaly detections ahead of the earthquake time of two (2) days. The correlated earthquakes were mainshocks of local magnitude 1.2 to 3.6, with epicenters within 40 𝑘𝑚 from the Gallicano site. Correlations among rainfalls, 𝐶𝑂 2 concentrations and earthquakes were also considered, showing that only few rainfall events were followed by a 𝐶𝑂 2 anomaly, mostly a day late. Description of the study area Eliminato: 2018 Eliminato: Methods 2017-2021 period. The structures identified by the DISS Working Group (2021) are also shown (blue rectangles: 146 Composite Seismogenic Sources; yellow rectangles: Individual Seismogenic Sources; blue curved lines: 148 Subduction Sources). Red dots are 𝑀 𝑤 >6 earthquakes extracted from the CPTI15 v 4.0 catalog (Rovida et al., 2022).